(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters as follows:The first chapter: It includes the research problem that appeared through the practice of the physical education teacher in his work for different types of pressures that cause him various troubles, whether internal or external, because in the end it has negative repercussions on him, whether psychologically, materially or socially, which prompted the researcher to conduct this search . As for the importance of the research: it is represented in the fact that:1- It is concerned with the issue of managing work pressures affecting the behavior of the physical education teacher.2- The need to know the principals at the different organizational levels, and the sources of pressures that teachers of physical education are exposed to.As for the research objective: it aims to build a scale for managing work stress for teachers of physical education